MODEL PENENTUAN KINERJA GURU BERBASIS ADAPTIVE NEURO FUZZY INFERENCE SYSTEM: STUDI KASUS SMK POLIMEDIK DEPOK - DEWI LEYLA RAHMAH (Faktor Exacta, 2014)
To determine teachers’ achievement is the one approach that can be done using fuzzy logic. With such an approach is expected to be able to choose achievement with effective teacher. Constraints faced is the lack of information system that can specifically provide support for decision makers, namely the principal, making it difficult to produce an optimal decision. Criteria determinig the teachers’ achivement is uses modeling based Adaptive Neuro Fuzzy Inference System. With the help of software Matlab the made a decision support system in terms of determining the outstanding teacher. The result of this research is where the determination of outstanding teacher at SMK Polimedik Depok more objective and more efficient decision making. Key Words: Teacher, Supervision, Performance, Metode Adaptive Neuro Fuzzy Inference System, Matlab